Hubungan Antara Gaya Hidup Sebagai Faktor Risiko Diabetes Melitus Tipe 2 Dengan Profil Glukosa Darah dan Tinjauannya Menurut Pandangan Islam - Farisi, Elbi Lazuardi Al; Purnamasari, Endah; Maharsi, Eri Dian; Karimulloh, Karimulloh (Syntax Corporation, 2025)
Diabetes Mellitus Type 2 (DM Type 2) is a chronic metabolic disease caused by insulin resistance. According to the International Diabetes Federation (IDF) 2021, Indonesia has around 14.3 million undiagnosed cases, particularly among the youth. Lifestyle factors, including physical activity and dietary patterns, are major risk factors. Medical students are vulnerable to diabetes due to academic pressure and sedentary lifestyles. In Islam, maintaining health is a responsibility aligned with the principle of ḥifẓ al-nafs. This study aims to provide a basis for education and encourage students to adopt healthy lifestyles. The methodology used is quantitative observational analytic with a cross-sectional approach, collecting data from 92 students at YARSI University’s Faculty of Medicine. Results indicate that the majority have moderate physical activity and poor dietary habits. Analysis using the Chi-Square test shows a significant relationship between random blood glucose (RBG) and dietary patterns (p=0.001), but no significant relationship with physical activity or smoking behavior. During Ramadan, no significant relationship was found between fasting blood glucose (FBG) and physical activity or smoking behavior. These findings emphasize the importance of dietary habits in managing blood glucose levels among students.